1999
DOI: 10.1099/00221287-145-9-2443
|View full text |Cite
|
Sign up to set email alerts
|

Identification of O-antigen polymerase transcription and translation start signals and visualization of the protein in Salmonella enterica serovar Typhimurium

Abstract: The wzy/rfc gene, encoding the O-antigen polymerase, of Salmonella enterica serovar Typhimurium has been previously cloned and sequenced. In the present work, the wzy transcriptional startpoint was initially identified by primer extension. Next, wzy promoter strength in Escherichia coli K-12 was measured, and was found to be greater than that of the induced lac promoter. To define the Wzy translational startpoint, DNA including the wzy promoter and the putative first five residues of the Wzy protein was fused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…It has been reported that the G ϩ C content of the coding region of O-antigen polymerase is generally lower than that of the bulk DNA of the bacterium (27,47). Indeed, the deduced G ϩ C content of the putative O-antigen polymerase in F. tularensis LVS was 23%, a value lower than that of the bacterium itself (33.2%) (12).…”
Section: Analysis Of F Tularensis Putative O-antigen Polymerase (Wzy)-mentioning
confidence: 95%
See 2 more Smart Citations
“…It has been reported that the G ϩ C content of the coding region of O-antigen polymerase is generally lower than that of the bulk DNA of the bacterium (27,47). Indeed, the deduced G ϩ C content of the putative O-antigen polymerase in F. tularensis LVS was 23%, a value lower than that of the bacterium itself (33.2%) (12).…”
Section: Analysis Of F Tularensis Putative O-antigen Polymerase (Wzy)-mentioning
confidence: 95%
“…Studies of O-antigen polymerases of many bacteria are hindered by the absence of a conserved region within and between species, an inability to recombinantly express in vitro the protein because of its hydrophobicity, the higher rate of use of rare codons, and a weak ribosomal binding site (47). Differences in primary amino acid sequences are probably necessary because Wzy recognizes cognate O-units that usually differ significantly in structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The S. enterica sv. Typhimurium Group B O antigen is an ideal candidate for Wzx topology studies as the gene cluster involved has been sequenced (Jiang et al, 1991), and it is one of the few for which all the biosynthesis proteins involved have been identified, these being for (1) nucleotide sugar biosynthesis of dTDP-rhamnose Nikaido et al, 1966;Graninger et al, 1999), GDP-mannose (Elling et al, 1996) and CDP-abequose (Wyk & Reeves, 1989), (2) the initial transferase WbaP (Wang & Reeves, 1994;Wang et al, 1996), for galactose phosphate, and the other three transferases WbaN, WbaU and WbaV, which are responsible for the respective addition of rhamnose, mannose and abequose residues (Liu et al, 1993(Liu et al, , 1995 and (3) the O-unit-processing proteins Wzx (Feldman et al, 1999;Marolda et al, 2004), Wzy (Collins & Hackett, 1991;Wong et al, 1999) and Wzz (Murray et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that the differences in O-antigen chain length distribution were related to the oligomeric composition of the specific Wzz protein, with Wzz molecules forming larger oligomers, and thus being able to recruit greater numbers of Wzy polymerases for continuous polymerization of the O-antigen (Morona et al, 2009). Nevertheless, the stoichiometric cellular distribution of Wzz with respect to Wzy polymerases does not align well with the proposed mechanism as it is well established that Wzz proteins are far more abundant than Wzy polymerase (Wong et al, 1999;Carter et al, 2009).…”
Section: Proposed Models Of O-antigen Chainlength Regulation In the Wmentioning
confidence: 96%